Sources of income growth and inequality across ethnic groups in Malaysia, 1970-2000 - Saari, Mohd Yusof; Dietzenbacher, Erik; Los, Bart (Pergamon Press, 2015)
This paper examines the sources of income growth for major ethnic groups in Malaysia. An input–output structural decomposition analysis is extended and applied to the social accounting matrices of 1970 and 2000. The results indicate that the expansion of exports and the changes in the compensation of labor and capital inputs are the main determinants for the income changes. The effects differ largely between rural and urban areas, between skilled and unskilled workers, and between the major ethnic groups. The combination of these two determinants, however, is a dominant factor in explaining the increase in income inequality in Malaysia.